Roles of GR Isoforms and Hsp90-binding Immunophilins in the Modulation of Glucocorticoid Biological Responses - Ciucci, Sol M.; Mazaira, Gisela I.; Galigniana, Mario D. (Current Reviews in Clinical and Experimental Pharmacology, 2023)
Glucocorticoid steroids play cardinal roles during the life span of an individual, modulating almost all aspects of the physiology, including the metabolism of carbohydrates, lipids and amino acids, as well as the immune response, neurological biology, stress adaptation, apoptosis, cell division, cell fate, inflammatory responses, etc. Glucocorticoids exert their biological effects by activation of the glucocorticoid receptor (GR), a bona fide ligand-activated transcription factor belonging to the nuclear receptor superfamily. The GR is expressed in virtually all cells of the human body showing isoformic versions and also transcription variants. GR forms oligomeric heterocomplexes that include the 90-kDa heat-shock protein (Hsp90) as an essential hub of the chaperone oligomer. The nature of chaperones associated with this heterocomplex is responsible for the modulation of the subcellular localization of the GR and its biological actions in a given tissue or cell type. In this sense, the discovery that immunophilins containing tetratricopeptide repeats (TPR) domains are responsible for the GR cytoplasmic transport mechanism and the nuclear retention half-time of the receptor opened new trends in our understanding of its complex mechanism of action. Because the properties of GR ligands influence these protein-protein interactions, specific steroid•receptor complexes may confer the GR different features providing new therapeutic opportunities to manage the disease. In this article, we analyze multiple aspects of the GR mechanism of action, some properties of the GR isoforms, and the latest findings revealing the roles of Hsp90-binding immunophilins to manage the glucocorticoid biological response.
Keywords: Glucocorticoid receptor